Methods of the policy process - Weible, Christopher M.; Workman, Samuel
The increasingly global study of policy processes faces challenges with scholars applying theories in radically different national and cultural contexts. Questions frequently arise about how to conduct policy process research comparatively and among this global community of scholars. Methods of the Policy Process is the first book to remedy this situation, not by establishing an orthodoxy or imposing upon the policy process community a rigid way of conducting research but, instead, by allowing the leading researchers in the different theoretical traditions a space to share the means by which they put their research into action.